An incremental dual-task paradigm to investigate pain attenuation by task difficulty, affective content and threat value. - Quoc C Vuong; Angela Owen; Kehinde Akin-Akinyosoye; Vera Araujo-Soares (PLoS ONE, 2018)
There is accumulating evidence that task demands and psychological states can affect perceived pain intensity. Different accounts have been proposed to explain this attenuation based either on how limited attentional resources are allocated to the pain stimulus or on how the threat value of the pain stimulus biases attention. However, the evidence for both proposals remains mixed. Here we introduce an incremental dual-task paradigm in which participants were asked to detect pain on their fingertip without any additional tasks during baseline phases or while concurrently detecting visual targets during task phases. The force applied to participants' fingertip in all phases increased incrementally until they detected moderate pain. In Experiment 1, we used coloured shapes and in Experiment 2 we used affective images as visual targets. We also manipulated the threat value of the pain stimulus in Experiment 2. For both experiments, we found that a concurrent task attenuated perceived pain intensity: mean force was significantly greater for the same moderate pain during task compared to baseline phases. Furthermore although task difficulty and affective content did not affect pain perception, the threat value of the pain stimulus moderated the magnitude of pain attenuation.